Barriers and facilitators to preparing families with premature infants for discharge home from the neonatal unit. Perceptions of health care providers - Raffray, Marie; Semenic, Sonia; Osorio Galeano, Sandra; Ochoa Marín, Sandra Catalina (Investigación y Educación en Enfermería, 2014)
Objective. To explore Colombian health care provider perceptions of barriers and facilitators to preparing families with premature infants for discharge home from the neonatal intensive care unit (NICU). Methodology. Using a qualitative descriptive design, in-depth semi-structured interviews were conducted with fifteen neonatal health care providers (HCPs) in Colombia. Data were analyzed using qualitative content analysis. Results. Participant responses centered on three main themes: 1) establishment of the parent-infant bond, 2) acquisition of parenting skills, and 3) getting ready for the transition from hospital to home. Barreirs to preparing parents for NICU discharge included obstacles to parental visiting in the NICU, communication barriers, difficulties related to the establishment of successful breastfeeding, insufficient human resources and poor links between hospital and community-based resources. Facilitators included the availability of social aids for vulnerable families, 24-hour telephone access to the neonatal units, tailored educational materials and group sessions, continuing education for staff and the community-based Kangaroo Program available to parents post-discharge. Adolescent mothers, indigenous parent and working fathers were identified as particularly challenging to reach and engage in discharge preparation. Conclusion. Neonatal HCPs identified numerous challenges as well as helpful strategies for preparing families for hospital discharge. Additional studies are needed on the experience of neonatal discharge from the perspective of parents of premature infants in Colombia, to help inform optimal interventions for supporting families during the transition from hospital to home. How to cite this article: Raffray M, Osorio S, Ochoa SC, Semenic S. Barriers and facilitators to preparing families with premature infants for discharge home from the neonatal unit. Perceptions of health care providers Invest Educ Enferm. 2014; 32(3):